Micro- and Nanowear of Self-Mated Steel Generated and Studied With an AFM at the Single Asperity Level - Reichelt, Manuel; Cappella, Brunero (Frontiers in Mechanical Engineering, 2021)
Single asperity nanowear phenomena are fundamental for understanding basic tribological mechanisms. Yet, they are studied mostly through theoretical and simulation works. Few experiments were conducted in the past decades, but usually with materials, which are commonly used in micro- and nanotechnology, but not for macroscopic components with relevance in tribology. In the present work, we show for the first time tribotests performed with self-mated 100Cr6 steel, a very widespread material at the macroscale, taking advantage of an AFM, employed as a tribometer for the tribotests as well as for the inspection of wear of both tribopartners. Emphasis is put on the morphology of the scars, on wear particles, and on wear of the “colloidal” particles glued on the AFM cantilever. Measurement demonstrate the possibility of characterizing single asperity events leading to very small wear (scars with isolated, down to 1 nm deep scratches). We highlight several phenomena, e.g. transfer of wear particles and their negative contribution to wear volume, which are elementary key constituents of tribological processes. Such phenomena, probably occurring also at the macroscale, can be detected, identified, and characterized with high spatial and time resolution only at the nanoscale, thus giving insight into conditions and causes of their emergence.